Hydrothermal system of the Papandayan Volcano, West Java, Indonesia and its geochemistry evolution of thermal water after the November 2002 eruption - Mazot, Agnes; Bernard, Alain; Sutawidjaja, Igan Supriatman (Geological Agency, 2007)
http://dx.doi.org/10.17014/ijog.vol2no1.20072Papandayan is a strato volcano situated in West Java, Indonesia. After the last magmatic eruptionin 1772, only few phreatic explosions have been occurring. At the present time, the activity is centeredin the northeast crater manifested by the presence of fumaroles and hot springs. In November 2002an explosive eruption occurred and ejected ash and altered rocks. Study of the altered rocks revealedthat an advanced argillic alteration took place in the hydrothermal system by an interaction betweenacid fl uids and rocks. Four zones of alteration have been formed as a limited extension along faults oracross permeable structures at different levels beneath the active crater of the volcano.Two types of acid fl uids are distinguished in the crater of the Papandayan Volcano: (1) acidsulphate-chloride water with pH values between 1.6 and 4.6, and (2) acid sulphate water with pHvalues between 1.2 and 2.5. The samples collected after the eruption revealed an increase in the SO4/Cl and Mg / Cl ratios. This evolution is likely explained by an increase in the neutralization of acidfl uids which tends to show that water-rock interactions were more signifi cant after the eruption. Thechanges in chemistry observed in 2003 were the consequence of the opening of new fractures whereunaltered or less altered volcanic rocks were in contact with the ascending acid water. The high Î´34Svalues (9-17â°) observed in the acid sulphate-chloride water before the November 2002 eruptionsuggest that dissolved sulphates were mainly formed by the disproportionation of magmatic SO2. Onthe other hand, the low Î´34S values (-0.3-7 â°) observed in acid sulphate-chloride water sampled afterthe eruption suggest that the origin of dissolved sulphates for these waters is the surfi cial oxidation ofhydrogen sulphide.